Manufacture of low thermal conductivity cordierite ceramic foam based on low-cost waste and raw materials - Esmat M. A. Hamzawy; Bassem S. Nabawy; Gehan T. El-Bassyouni; Zeinab A. Abd El-Shakour (Scientific Reports)
Abstract Magnesite, silica fumes, and aluminum slag were used to create foam cordierite ceramic material. During the sintering process, cordierite ceramic was formed at temperatures between 1200° and 1350°C. Between 1250° and 1300°C during the sintering process, the samples experienced swelling and an increase in porosity. However, the existence of holes and tiny openings in the samples indicates an alteration in their overall microstructure. Scanning electron microscopy (SEM) reveals that the pore size increases at elevated sintering temperatures, particularly at 1300°C. The submicron and nanoscale particles are dispersed within a glassy matrix. The apparent density and specific gravity values range from 0.498 to 1.501 g/cm3 and from 1.677 to 2.996 g/cm³, respectively. The measurements were conducted on foam samples molded at 20 and 30 kN, revealing a little rise in the apparent density and a decrease in porosity with the elevation of molding pressure. The apparent density (ρb) and the porosity values (∅He, 48.22–83.16%.) are directly and inversely proportional correlations to the thermal conductivity (R² = 0.982 & R² ≥ 0.963, respectively). Furthermore, the thermal conductivity is controlled positively by the thermal diffusivity (1.192 ≤ ∝ ≤ 1.882 mm²/s, R² ≥ 0.848) and heat capacitance (604.9 ≤ Cp ≤ 841.4 J/(K·kg), R² ≥ 0.946). This lightweight ceramic foam, once sintered at 1300°C, serves as an effective heat insulator, which appears to be the optimal temperature for achieving superior thermal properties in insulating cordierite foam.